Pendekatan Diagnosis Avian Influenza Virus dan Newcastle Disease Virus pada Kasus Lapangan Ayam Petelur: Imunopatologis Streptavidin Biotin - Maya Ekaningtias; Hastari Wuryastuty; Wasito Wasito (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
Poultry can be infected not only by one type of virus, but also by more than one type of virus. Avian influenza virus (AIV) and Newcastle disease virus (NDV) are two important pathogens in poultry that can cause recurrent outbreaks and often lead to clinical symptoms and pathological lesions similar in poultry with high morbidity and mortality causing significant economic losses to the poultry industry. This study aims to detect and differentiate pathogenic viruses in commercial laying chickens with similar clinical symptoms, especially torticolis and curled toe paralysis, and anatomic pathological lesions, such as foci necrotic hemorrhages in the digestive tract by applying streptavidin-biotin immunohistochemical immunological test (IHC SB). Samples (chickens) were taken from the cases of the disease in poultry in several commercial poultry farms. The layer chickens in which showed clinical symptoms of torticolis and curled toe paralysis, and hemorrhagic lesions in the lungs and / or digestive system are suspected of having AIV and NDV infections. After being necropsied, then lungs and gastrointestinal tract were tested IHC SB. The IHC SB results were examined with a digital microscope camera system. The results of the present study indicated that AIV antigen was detected in the lungs, but not in the digestive tract, whereas, NDV was detected in the digestive tract, but not in the lungs. It was concluded, that the IHC SB can be applied for confirmation of the diagnosis of AIV and NDV and indicated, that the commercial laying chickens with clinical symptoms of torticolis and curled toe paralysis, as well as pathological hemorrhagic lesions in the gastrointestinal tract could be infected by both viruses.